Opening Thinking Creativity in Concept Learning by use of Demonstration Method at Klass VI SDN 19 Kampung Jawa Kecamatan Tanjung Harapan Kota Solok - Cinto Buliah (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This research intent to increase activity and student studying result about debit concept. Base observation at the site writer is still less in apply mathematics learning concept at elementary school that is begun from concept, finding formula, analyse, and does reasoning, student feels mathematics learning be hard and many student didn't memorize multiple. This observational form is Observational Action Class. This research result two type data which is activity data studies and result data study. Activity data studies acquired student of observation that at o with quantitative approaching in shaped percentage. While result data studies to be gotten from result essays that executed on each cycle, as compared to KKM learning, to been worked through descriptive. Base analisis data,on cycle I (one) , successful student get more point and equal to 70 just 9 person of 17 students or 52,94 %, with yielding average value studies 65,29. On cycle II (two) experiences step-up,student that gets to above assess or equal to 70 have 16 person or 94,11 % by appreciative average usufructs to study 85,29 and student activity of 47% rise become 88%. Conclusion, with demonstration method can increase activity and studying result about student debit concept VI class SD Country 19 Kampung Jawa